India : Diagnostic Assessment of Select Environmental Challenges, Volume 2. Economic Growth and Environmental Sustainability, What Are the Tradeoffs? - World Bank (Washington, DC, 2013)
This report provides estimates of social and financial costs of environmental damage in India from three pollution damage categories: (i) urban air pollution, including particulate matter and lead; (ii) inadequate water supply, poor sanitation, and hygiene; (iii) indoor air pollution; and four natural resource damage categories: (a) agricultural damage from soil salinity, water logging, and soil erosion; (b) rangeland degradation; (c) deforestation; and (d) natural disasters. The estimates are based on a combination of Indian data from secondary sources and on the transfer of unit costs of pollution from a range of national and international studies. The quantification and monetary valuation of environmental damage involves many scientific disciplines including environmental, physical, and biological and health sciences, epidemiology, and environmental economics. Estimates of the costs of degradation are generally reported as a percent of conventional gross domestic product (GDP). This provides a useful estimate of the importance of environmental damages but it should not be interpreted that GDP will increase by a given percent if the degradation were to be reduced to zero. Any measures to reduce environmental degradation will have a cost and the additional cost goes up the greater is the reduction that is made. Hence a program to remove all degradation can well result in a lower GDP. This report provides a measure of the overall damage relative to a benchmark, in which all damages related to economic activity are eliminated. The report is structured as follows: section one provides a summary of estimated social and financial costs of environmental damage; section two focuses on urban air pollution; section three deals with water supply, sanitation, and hygiene; section four focuses on indoor air pollution; section five focuses on land degradation, crop production, and rangeland degradation; and section six deals with forest degradation.